Pengaruh Display Digital Ketersediaan Kamar Rawat Inap Terhadap Kemudahan Pasien - Rezky, Mutiara Cahaya; Firdaus, Muhammad; Zaky, Abdul; Suryandartiwi, Wiwik (Prodi Sistem Informasi Universitas Dharma Andalas, 2026)
This study aims to analyze the effect of digital display usage for inpatient room availability on patient convenience at Arifin Achmad Regional General Hospital, Riau Province. The research employed an analytic survey with a cross-sectional design using a Likert-scale questionnaire administered to 95 inpatients. Classical assumption tests indicated that the residuals were normally distributed and the regression model was appropriate. Multiple linear regression revealed that patient knowledge had a positive and significant effect on patient convenience (p<0.001), while hospital policy and data validity showed no significant effect. Simultaneously, the model was significant (F=94.206; p<0.001) with R²=0.756. These findings highlight that patient convenience is mainly influenced by patients’ knowledge of the digital display system. Hospitals need to strengthen patient education, improve internal policies, and enhance data accuracy to optimize the benefits of the system.